Kolaborasi POLRI & DISPENDA Kabupaten Keerom untuk Penertiban Sumber-Sumber Kebocoran Pendapatan Asli Daerah - Jaya, Muhammad Efendi; Rohrohmana, Basir (JURNAL EKOLOGI BIROKRASI, 2024)
This research examines the collaboration between the Indonesian National Police and the Keerom District Revenue Office in assessing and controlling local revenue leakage. The study uses qualitative descriptive methods and data from the post-reform period. Data is collected through purposive sampling, including interviews, observations, and documentation. The findings highlight the importance of collaboration between the Police and the Revenue Office in identifying and addressing revenue leakage issues. This collaboration involves task sharing, resource allocation, and coordination mechanisms. By working together, they can identify sources of leakage, evaluate the impact on local finances, and develop appropriate measures. The study concludes that this collaboration has positive effects on increasing local revenue, improving financial management efficiency, and enhancing public trust in local government. To further improve the welfare of people in Keerom Regency, concrete steps are needed to maintain and enhance this collaboration